PENERAPAN HUKUM MILITER TERHADAP ANGGOTA TNI DALAM KASUS TINDAK PIDANA INSUBORDINASI PADA DILMILTI II JAKARTA (Neolectura, 2024)
Insubordination is an act that is completely unacceptable in the military, because it is considered to have violated the Sapta Marga and the Soldier's Oath which are the basic reference for personality patterns as TNI soldiers. Acts against superiors should not be carried out in the military environment, because acts against superiors or insubordination are classified as serious crimes. For this reason, we will further examine the absolute competence of the High Military Court in handling Insubordination Crime Cases and how military law is applied to TNI members in cases of insubordination crimes at the Jakarta II High Military Court. The research method used in this research is a normative legal research method. From the research results it was found that the High Military Court is a Second Level Military Court which has the authority to hear appeals from First Level Military Court Decisions. Then the application of military law to members of the TNI in cases of criminal acts of insubordination at the Jakarta II High Military Court is basically the same as the First Level Military Court, namely based on the Military Criminal Code (KUHPM). The results of the DILMILTI decision can be different from those of the Military Court of First Instance due to differences in the opinions of the panel of judges, but can also have the same results because of the similarities in the analysis and opinions of the Panel of Judges so that the new decision actually strengthens the previous decision.